Examining the Consequences of Welfare Conditionality: A Case Study of Compulsory Income Management in the Regional Community of Ceduna, Australia. Issue 3 (25th July 2022) - Roche, Steven; Mendes, Philip; Marston, Greg; Bielefeld, Shelley; Peterie, Michelle; Staines, Zoe; Humpage, Louise
Abstract : Welfare conditionality, whereby eligibility for income support payments is linked to prescribed forms of behaviour or values, is intended to encourage responsible behaviour in marginalised populations. However in practice, it may have consequences that worsen rather than improve their life chances. One of the most invasive forms of conditional welfare is income management (IM), involving the quarantining of up to 90 per cent of income that cannot be spent on excluded items in order to reduce substance abuse and gambling and enhance financial management and parenting capacity. This qualitative study examines the views of IM participants and community stakeholders in the regional community of Ceduna, Australia. Its findings are presented – pertaining to practical experiences of IM, the impact of IM on participant wellbeing, and community divisions around IM – and the study discusses whether or not it has advanced key program objectives. It is concluded that the negative effects of IM exceed any perceived benefits.